Perbandingan aktivitas harian dua spesies lebah tanpa sengat di Sulawesi Barat: Comparison of daily activities of two species stingless bees in West Sulawesi - Hasan, Phika Ainnadya; Suhri, Andi Gita Maulidyah Indraswari; Putera, Alexander Kurniawan Sariyanto (Perhimpunan Entomologi Indonesia, 2024)
Stingless bees are spread across several islands in Indonesia, including Sulawesi. There have been no reports of daily activity of stingless bees in West Sulawesi Province. Therefore, this study aims to identify types of stingless bees in West Sulawesi, measure their daily activities, and their relationship with environmental parameters. The research was conducted in the highlands (Taupe Village, Mamasa Regency, 1,340 m dpl) and the lowlands (Mirring Village, Polewali Mandar Regency, 63 m dpl). Daily activity data collected which includes the activities in and out of the nest, carrying pollen, and throwing away rubbish. Daily activity observations use the scan sampling method. The results of the research show that the type of bee in Taupe Village is Wallacetrigona incisa (Sakagami & Inoue), while in Mirring Village is Tetragonula sapiens (Cockerell). There was no significant difference in the daily activity of W. incisa in the highlands and T. sapiens in the lowlands (P > 0.05). Significant differences were seen between the activities of leaving and entering the nest and the activities of carrying pollen and throwing away rubbish (P < 0.05). Wind speed is an environmental parameter that influences pollen-carrying activity in T. sapiens in the lowlands (r = 0.83; P = 0.002). Environmental parameters greatly influenced the daily activity of W. incisa at 12.00 pm, with an influence of 93% (P < 0.05). The results of this study indicate that differences in the type and habitat of bees and environmental factors cause differences in the daily activity of stingless bees.